The Drift of the Xsens Moven Motion Capturing Suit during Common Movements in a Working Environment - Damgrave, R. G. J.; Lutters, D. (Cranfield University Press, 2009)
When using inertial motion capturing technology, the accuracy of the results is strongly influenced by the socalled drift. This paper describes the drift of an Xsens Moven motion capturing suit during common movements, measured in a standard working environment. The test is performed in a room not shielded from magnetic disturbances, to acquire insight on how accurate the absolute position determination of the motion capturing system is during use in a standard environment. The test is performed by walking a path with the same start and end point, and reviewing the measured difference in the absolute position of one sensor.
Organised by: Cranfield University
Keywords: Motion Capturing; Inertial Sensoring; Accuracy